Understanding and governing sustainable tourism mobility : psychological and behavioural approaches - Cohen, Scott A.; Higham, James E. S.; Gössling, Stefan; Peeters, Paul (Contemporary geographies of leisure, tourism, and mobility., 2014)
"Despite a growing contribution to climate change, tourist and traveller behaviour is currently not acknowledged as an important sector within the development of climate policy. Whilst tourists may be increasingly aware of potential impacts on climate change there is evidence that most are unwilling to modify their actual behaviours. Influencing individual behaviour in tourism and informing effective governance is therefore an essential part of climate change mitigation. This significant volume is the first to explore the psychological and social factors that may contribute to and inhibit sustainable change in the context of tourist and traveller behaviour. It draws on a range of disciplines to offer a critical review of the psychological understandings and behavioural aspects of climate change and tourism mobilities, in addition to governance and policies based upon psychological, behavioural and social mechanisms. It therefore provides a more informed understanding of how technology, infrastructure and cost distribution can be developed in order to reach stronger mitigation goals whilst ensuring that resistance from consumers for socio-psychological reasons are minimized.Written by leading academics from a range of disciplinary backgrounds and regions this ground breaking volume is essential reading for all those interested in the effective governance of tourism's contribution to climate change now and in the future. "